Perceived invulnerability in traffic: illusion of control, desire for control, risk perception, and traffic-locus of control - Nae, Elena-Cristina; Truța, Camelia; Cazan, Ana-Maria (Frontiers in Public Health, 2025)
IntroductionThis study examined the psychological predictors of risky driving behavior, focusing on traffic-locus of control, illusion of control, desire for control, and risk perception—as key components of perceived invulnerability.MethodsTwo main hypotheses were tested: the first (H1) included two sub-hypotheses, H1a, that perception of invulnerability predicts risky driving, and H1b, that this relationship is moderated by driving experience; the second hypothesis (H2), was that risk perception mediates the relationship between traffic-locus of control, driving experience, and risky driving behaviors. A sample of 115 drivers completed standardized self-report questionnaires.ResultsResults partially supported the first hypothesis: perceived invulnerability, operationalized through illusion of control, desire for control, and risk perception predict risky driving behavior. However, driving experience did not moderate any of the observed relationships. The second hypothesis was also partially confirmed. A two-step mediation model revealed that traffic-locus of control and driving experience predicted risk perception, while the full model explained 47% of the variance in risky behavior. Risk perception partially mediated the relationship between beliefs about other drivers and risky driving. Additionally, beliefs in fate and luck were directly associated with lower risk engagement. Contrary to expectations, driving experience did not moderate any of the key relationships, suggesting that these psychological patterns remain influential regardless of experience level.DiscussionThese findings underscore the complex interplay between control beliefs and perceived risk in driving contexts, offering insights for interventions targeting cognitive distortions and overconfidence that contribute to hazardous driving practices.